A Rechargeable Aqueous Sodium‐Ion Battery. Issue 7 (5th April 2019) - Thimmappa, Ravikumar; Gautam, Manu; Aralekallu, Shambhulinga; Devendrachari, Mruthunjayachari Chattanahalli; Kottaichamy, Alagar Raja; Bhat, Zahid Manzoor; Thotiyl, Musthafa Ottakam
Abstract: We report a rechargeable sodium‐ion battery in an aqueous environment with hydrophobic few‐layer graphene as the capacitive anode and hexacyanometallate as the insertion cathode. Owing to the lack of hydrophilic functionalities, sodium‐ion adsorption is selectively favored over H + adsorption at the hydrophobic anode/electrolyte interface without the complexity of widely encountered hydrogen‐ion insertion/H2 evolution. Hydrophobicity precludes chemical bond formation with sodium ions, thereby improving reversibility and extended cyclability during charge discharge chemistry. Abstract : Do me a favor : A rechargeable aqueous sodium ion battery with hydrophobic few layer graphene as the capacitive anode and iron(II)hexacyanoferrate(III) as the insertion cathode. Hydrophobicity precludes chemical bond formation with sodium ions and favors selective sodium ion adsorption over widely encountered H + ion adsorption/H2 evolution.